Pencegahan Penularan Covid-19 melalui Pembagian Masker dan Desain Infografis di Pasar Badung, Denpasar-Bali - Made Arini Hanindharputri; A.A Sagung Intan Pradnyanita; Sri Utami (Universitas Mataram, 2021)
The COVID-19 pandemic, which has hit almost all countries in the world, requires all people to comply with health protocols to face new life, such as using masks in everyday life. In Denpasar, Bali itself, the number of COVID-19 transmissions continues to increase, so masks are mandatory items that must be owned by the community. However, conditions in the field, there are still many people who do not use masks in their daily activities, such as at Badung Market, Denpasar. The market as a place of buying and selling that involves the interaction of many people, should have more health protocols so that it does not become a new cluster in the spread of COVID-19. Therefore, community service was made by involving lecturers and students of all Study Programs at the Bali Design and Business Institute, in the form of distributing cloth masks and infographics to provide education to the public, especially traders and the community in the Badung Market area, Denpasar-Bali. The methods used are choosing the location for distributing masks, collecting cloth materials for mask production, producing masks, designing infographics and mask packaging, packaging, and distributing masks in the Badung Market area. The resulting cloth masks are packaged together with infographics, so that people can easily get education on preventing COVID-19 by using masks.